REORIENTASI PERAN DAN TANTANGAN PENDIDIKAN AGAMA ISLAM DI TAPANULI TENGAH - Harahap, Pandapotan; Prasetia, Indra; Pasaribu, Munawir (Berajah Journal, 2025)
This study examines the role and challenges faced by Islamic religious education in Tapanuli Tengah. The objectives of this research are to understand the state of Islamic religious education in the region and to analyze its role and the challenges it encounters. The study employs a qualitative research method with a case study approach, collecting data through interviews conducted in schools or madrasas that represent the geographical conditions of the area. The research focuses on five senior high school-level institutions, Several key findings were identified. In Tapanuli Tengah, some schools have implemented programs to support the development of Islamic religious education, such as monthly religious study sessions (pengajian), communal religious obligations (fardhu kifayah), and extracurricular activities through the Islamic Student Organization (ROHIS) in Madrasah Aliyah. Additionally, some of the observed schools have incorporated technology into their teaching processes to enhance innovation and student engagement, However, challenges remain. Some students still exhibit low interest in Islamic religious education, attributed to rapid technological advancements and the widespread use of gadgets, which divert their attention away from classroom learning. This has led to a paradigm shift from doctrinal teaching methods to contextual, technology-based learning approaches rooted in local wisdom. Strengthening Islamic religious education requires synergy among schools/madrasas, families, and communities to ensure students remain guided and shielded from the negative impacts of social media.